LITERASI NUMERASI DIKAJI DARI PENALARAN MATEMATIS SISWA DALAM MATERI BILANGAN DI SMP - Rasita, Rasita; Jamiah, Yulis; BS, Dian Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
One of the most essential fundamental literacy skills for students to master is numerical literacy. A person"™s numeracy literacy will be good if it is supported by good reasoning too. This research aims to explain how students' ability to reason mathematically about numbers is used to measure numeracy literacy. The technique utilized in this research is a qualitative method with a descriptive research form. A number-related literacy test and interviews were used as the research instruments. This study included 26  students of class VIII  from SMP Negeri 22 Pontianak as participants. 3  students with high mathematical reasoning, 3  students with moderate mathematical reasoning, and 3  students with low mathematical reasoning were selected to be interviewed out of the 26 students. According to the findings of the study, students' mathematical reasoning in relation to numbers in class VIII at SMP Negeri 22 Pontianak is used to assess numeracy literacy. Of the 26 students, 4 had high mathematical reasoning, 17 had moderate mathematical reasoning, and 5 had low mathematical reasoning.